TRAINING NEEDS ANALYSIS OF FILIPINO COMMUNTIY OFFICIALS: EVIDENCE FROM UNIVERSITY EXTENSION PROJECT - Inero Ancho; Rowena Hibanada; Bryan Dayuta; Kim Cataquian; Abegail Karen (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2022)
As the basic political unit in the Philippines, barangays are expected to exercise their power and authority in managing the interactions of the community members. This includes their knowledge, skills, and competencies to exercise their oath of office, without compromising the needs of the constituents as a public trust. This research aims to measure the knowledge of the barangay officials in their duties, not limited to the mandated roles, the research also tackled the extent of their orientation to Sustainable Development Goals (SDGs) and lifelong learning as these emphasize the prevalent concerns present in countries, identified by intergovernmental organizations. Governance, including procedures, technicalities, and duties, plays a vital role in the harnessing the assets present in the localities towards participatory and societal development. Capacity-building, through offering a certificate program was seen as an aid to empower the barangay leaders to realize their role as catalysts of change in their barangays.